2008
DOI: 10.1021/cb700211s
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Probes of Bacterial Signal Transduction Reveal That Repellents Stabilize and Attractants Destabilize the Chemoreceptor Array

Abstract: The signal transduction cascade responsible for bacterial chemotaxis serves as a model for understanding how cells perceive and respond to their environments. Bacteria react to chemotactic signals by migrating toward attractants and away from repellents. Recent data suggest that the amplification of attractant stimuli depends on receptor collaboration: occupied and unoccupied chemoreceptors act together to relay attractant signals. Attractant signal transmission, therefore, depends on the organization of the c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
27
0

Year Published

2008
2008
2013
2013

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(27 citation statements)
references
References 58 publications
0
27
0
Order By: Relevance
“…Affecting the dynamics of the HAMP domain could be an effective tool to modulate the whole transducer signaling domain dynamics. This would easily lead to changes in the interaction between dimers within the chemoreceptors trimers (52) and also in the cluster super-structure suggested for the chemo-and photoreceptors, an assumption for which now experimental evidence also exists (49). Future NMR and sitedirected spin labeling EPR experiments will unravel the functional and molecular details of the transition between different dynamic states of HAMP domains.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Affecting the dynamics of the HAMP domain could be an effective tool to modulate the whole transducer signaling domain dynamics. This would easily lead to changes in the interaction between dimers within the chemoreceptors trimers (52) and also in the cluster super-structure suggested for the chemo-and photoreceptors, an assumption for which now experimental evidence also exists (49). Future NMR and sitedirected spin labeling EPR experiments will unravel the functional and molecular details of the transition between different dynamic states of HAMP domains.…”
Section: Discussionmentioning
confidence: 95%
“…In fact, the notion that a two-state equilibrium between populations with different degrees of dynamics can be the language of the activation/deactivation of the cytoplasmic domain was again put forward by Hazelbauer et al (48). Recently, evidence for a stabilization/ destabilization mechanism for the bacterial signal transduction were also provided in vivo (49).…”
Section: Discussionmentioning
confidence: 99%
“…Consistent with this model, the activity of the CheA kinase in E. coli was found to increase as the density of receptors increases (13,14). In further support of this model for clustering and kinase regulation, multivalent ligands that destabilized the clusters in E. coli behaved as attractants, whereas ones that stabilized the clusters behaved as repellents (15,16).…”
mentioning
confidence: 67%
“…Studies where attractant binding was found to reduce polar receptor clustering employed immunofluorescence (12,15). Those studies that failed to observe any changes in receptor clustering employed live cell microscopy and fluorescent protein fusions (17,18,21).…”
Section: Live Cell Fluorescence Microscopy Also Demonstrates That Attmentioning
confidence: 99%
“…There is resonance here with a series of studies of the cluster of receptors responsible for chemotaxis in bacteria, the most recent of which by Borrock et al appears on page 101 of this issue (6). Many bacteria move in response to their chemical environment by the mechanism of chemotaxis, which involves a two-component signal transduction system.…”
mentioning
confidence: 99%